2007
DOI: 10.1097/bot.0b013e31806dd93b
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Suture Anchors to Repair the Ruptured Quadriceps Tendon

Abstract: Quadriceps tendon rupture is an incapacitating injury that usually requires surgical repair. Traditional repair methods involve transpatellar suture tunnels, but recent reports have introduced the idea of using suture anchors to repair the ruptured tendon. We present 5 cases of our technique of using suture anchors to repair the ruptured quadriceps tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Hart investigated biomechanical differences between trans-osseous equivalent double-row suture anchor and trans-osseous tunnel repair: he reported that both were effective in terms of strength, repair stiffness and gap formation with similar results, but the transosseous repairs were stronger 28 . Lighthart et al found no significant differences in terms of displacement after 1000 cycles, adding that suture anchors are more expensive but, as confirmed also by Richards et al 24 , Maniscalco et al 25 and Bushnell et al 26 , allow a smaller skin incision and reduce operative times 29 . For delayed repair and re-ruptures are suggested Scuderi technique 4 to reinforce and Codivilla technique to lengthen the tendon.…”
Section: Quadriceps Tendon Tear Rupture In Healthy Patients Treated Wmentioning
confidence: 87%
See 1 more Smart Citation
“…Hart investigated biomechanical differences between trans-osseous equivalent double-row suture anchor and trans-osseous tunnel repair: he reported that both were effective in terms of strength, repair stiffness and gap formation with similar results, but the transosseous repairs were stronger 28 . Lighthart et al found no significant differences in terms of displacement after 1000 cycles, adding that suture anchors are more expensive but, as confirmed also by Richards et al 24 , Maniscalco et al 25 and Bushnell et al 26 , allow a smaller skin incision and reduce operative times 29 . For delayed repair and re-ruptures are suggested Scuderi technique 4 to reinforce and Codivilla technique to lengthen the tendon.…”
Section: Quadriceps Tendon Tear Rupture In Healthy Patients Treated Wmentioning
confidence: 87%
“…Anchors repair has recently been described by different authors [24][25][26] . Biomechanical studies were performed and showed no significant difference between anchor repair and patellar drilling holes technique 27 .…”
Section: Quadriceps Tendon Tear Rupture In Healthy Patients Treated Wmentioning
confidence: 99%
“…Surgical repair is widely recommended for cases of complete rupture to prevent long term functional impairment [3,4,5,8,11-13]. Partial ruptures are those that do not involve the whole tendon mass and there is less consensus regarding the management of these tears.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally used surgical repair techniques have included direct suture repair; using drilled suture tunnels in the patella; the Scuderi technique for augmentation of direct repairs and the Codivilla lengthening technique used in shortened chronic tears [4,5,8]. More recently, fixation of the tendon with suture anchors on the patella combined with soft tissue reinforcement has been used with good results [11,13]. We chose to use suture anchors pre-loaded with Orthocord because being partially absorbable it would provide prolonged support to the tendon repair which would have to resist high volume dynamic loading as our patient recommenced training.…”
Section: Discussionmentioning
confidence: 99%
“…Of those partial tears, 7 were off the superior pole of the patella, 1 from the vastus medialis, 1 from the rectus femoris, and 1 was a midsubstance tear ( Table 2). Of the 9 complete tears, 6 were from the superior pole of the patella, 2 from the vastus medialis, and 1 was a midsubstance ( Table 2) The QT was repaired in two main methods, suture Anchor or Trans-Osseous repair (ATO) 9 (1 anchor, 5 trans-osseous) and End to End (EE) (13 patients) [5,6]. Of the ATO repairs, 4 were complete tears, with only suture anchor repair being done on one of the two partial tears in this group ( Table 2).…”
Section: Surgical Findingsmentioning
confidence: 99%